Home Garden of Local Community in Pancasila Village for Biodiversity Conservation and Ecotourism Sites Development in Tambora Geopark, Sumbawa Island - Luchman Hakim; Hong Sun Kee (Journal of Tropical Life Science, 2018)
Home gardens of the villages near the conservation area plays an important role, both in ecologicl and socio-economical aspects. The aim of the research is to identify the plant species diversity in home garden in Pancasila Village, Tambora Geopark in Sumbawa Islands. Floristic survey was conducted at 25 home gardens on local community. An in-depth interviews with informant was generated to generate informationÂ related to species value and home garden management. Data was analyzed disruptively. Result of the study shows that 87 plant species (46 families) was grows in home gardens. These plants consist of 49.56 % of Phanerophytes, 8.90% of Chamaephytes, 25.28% of Â Hemicryptophytes and 6.70%of Cryptophytes. According to phytogeograpical origins, 24.41% of the species exclusively are Asian tropic species. These plant has numerous purposes, including staple food, species and vegetables, fruit trees shading trees and ornamental plants. From all species in home garden, some plant has high frequency, including Nephelium lappaceum (f = 0.52), Bougainvillea spectabilis (f = 0.40), Mangifera indicaÂ (f = 0.36), Musa paradisiaca (f = 0.36) and Coffea sp. (f = 0.32). Most of the species was identified as exotic plant species and therefore attention to such species group is needed to protect the environment and biodiversity of Tambora geopark.